Sensorless Control of PMSM for base speed range using Two-Degree-of-Freedom MTPA current control and HF test current injection for low speed range - Seilmeier, Markus; Piepenbreier, Bernhard (2014)
In this paper a recently published innovative sensorless Two-Degree-of-Freedom current control scheme for the whole speed range is extended for a maximum torque per ampere (MTPA) control. Saturation is taken into account for the calculation of the MTPA trajectory by use of current dependent machine parameters which were identified beforehand. For low and zero speed operation test current injection is used to gain a position error signal. Sensorless control performance is deteriorated by cross-saturation and higher harmonic saliencies which are considered by current and position dependent inductances. A flatness based test signal pre-control provides compensation for those secondary saliencies. For mid and high speed operation the model based dynamic feed forward control is modified in order to achieve a high quality position error signal from the tracking controller. Like this no additional model based estimator evaluating back-EMF information is needed. The proper functioning of the proposed method is proven by experimental results.
Keywords: permanent magnet motors; sensorless control; maximum torque per ampere (MTPA); magnetic saturation; saliency; test current injection; Two-Degree-of-Freedom control